Immunohistochemical angiogenic biomarkers in hepatocellular carcinoma and cirrhosis: correlation with pathological features (Clinics, 2016)
OBJECTIVE To investigate immunohistochemical markers of angiogenesis and their association with pathological prognostic features in hepatocellular carcinoma and cirrhotic liver. METHODS Vascular endothelial growth factor, CD105, and cyclooxygenase-2 were immunohistochemically detected in 52 hepatocellular carcinoma tissue samples and 48 cirrhotic liver tissue samples. Semiquantitative measurements of vascular endothelial growth factor and cyclooxygenase-2 were evaluated considering the degree and intensity of immunostaining based on a 7-point final scoring scale. CD105 microvascular density (MVD-CD105) was measured using automated analysis. Morphological aspects evaluated in the hepatocellular carcinoma samples included size (≤2 and >;2 cm), differentiation grade, and microvascular invasion. RESULTS The mean vascular endothelial growth factor immunoreactivity score was slightly higher in the hepatocellular carcinoma samples (4.83±1.35) than the cirrhotic liver (4.38±1.28) samples. There was a significant and direct correlation between these mean scores (rs=0.645, p=0.0001). Cyclooxygenase-2 was expressed in all the cirrhotic liver samples but was only found in 78% of the hepatocellular carcinoma samples. The mean cyclooxygenase-2 score was higher in the cirrhotic liver samples (4.85±1.38) than the hepatocellular carcinoma samples (2.58±1.68), but there was no correlation between the scores (rs=0.177, p=0.23). The mean CD105 percentage in the hepatocellular carcinoma samples (11.2%) was lower than that in the cirrhotic samples (16.9%). There was an inverse relationship in MVD-CD105 expression between the hepatocellular carcinoma and cirrhotic samples (rs=-0.78, p=0.67). There were no significant associations between vascular endothelial growth factor expression and morphological characteristics. Cyclooxygenase-2 and CD105 were associated with hepatocellular carcinoma differentiation grade (p=0.003 and p=0.05, respectively). CONCLUSION Vascular endothelial growth factor, cyclooxygenase-2, and MVD-CD105 were highly expressed in cirrhotic liver compared to hepatocellular carcinoma and might be involved in liver carcinogenesis. Additionally, cyclooxygenase-2 and CD105 might be involved in hepatocellular carcinoma differentiation grade.